Baseline factor VIII plasma levels and age at first bleeding in patients with severe forms of von Willebrand disease. (4th February 2016) - Siboni, S. M.; Biguzzi, E.; Caiani, V.; Mistretta, C.; Bucciarelli, P.; Peyvandi, F.
Abstract : Introduction: von Willebrand disease (VWD) is the most common inherited bleeding disorder. The age of bleeding onset is highly variable, also in patients with similar degree of severity. Aim: The primary aim of this study was to evaluate whether baseline factor VIII (FVIII) plasma levels correlate with age at first bleeding in patients with extremely low levels of VWF:RCo (<6 IU dL −1 ). Methods: One hundred and three patients with VWF:RCo <6 IU dL −1 (6 VWD1, 73 VWD2 and 24 VWD3) undergoing a medical examination between September 2010 and September 2013 were included. The relationship between baseline FVIII levels and age at first bleeding was tested in a multivariable linear regression model, adjusting for sex. Results: The median age at first bleeding was lower in patients with VWD3 than in those with severe forms of VWD1 or VWD2 (1 year vs. 7 and 8 years, respectively, P < 0.0001). A positive non‐linear relationship between FVIII levels and age at first bleeding was found, the latter increasing by 5 years for every 10 IU dL −1 increase of FVIII (β = 4.95 [95% CI: 2.02–7.87]) until levels of 30 IU dL −1, after which the age increased slowly. This relationship was not found in VWD 2A and 2B. In 65 patients (63%) there was a more than 6‐month delay between bleeding onset and VWD diagnosis, with no difference over decades. Conclusions: Baseline FVIII plasma levels influence the age at bleeding onset in VWD patients with extremely low levels of VWF:RCo, except in those with types 2A and 2B.